2014
DOI: 10.1021/am506971b
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Sorted Semiconducting Carbon Nanotube Networks for High-Performance Ambipolar Field-Effect Transistors

Abstract: Efficient selection of semiconducting single-walled carbon nanotubes (SWNTs) from as-grown nanotube samples is crucial for their application as printable and flexible semiconductors in field-effect transistors (FETs). In this study, we use atactic poly(9-dodecyl-9-methyl-fluorene) (a-PF-1-12), a polyfluorene derivative with asymmetric side-chains, for the selective dispersion of semiconducting SWNTs with large diameters (>1 nm) from plasma torch-grown SWNTs. Lowering the molecular weight of the dispersing poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
152
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(173 citation statements)
references
References 43 publications
13
152
0
Order By: Relevance
“…The sorted (7,5) SWNTs were dispersed from a mixture of nanotube chirality by exploiting the interaction between the nanotube and the side-chains attached to the PFO backbone. [18] It has F. Bottacchi et al Small (2016), DOI: 10.1002/smll.201600922 -5 -been previously shown that polyfluorene and its derivatives have the ability to selectively wrap and solubilize semiconducting SWNTs with specific diameters.…”
Section: (75) Swnt Dispersion and Morphological Characterizationmentioning
confidence: 99%
See 4 more Smart Citations
“…The sorted (7,5) SWNTs were dispersed from a mixture of nanotube chirality by exploiting the interaction between the nanotube and the side-chains attached to the PFO backbone. [18] It has F. Bottacchi et al Small (2016), DOI: 10.1002/smll.201600922 -5 -been previously shown that polyfluorene and its derivatives have the ability to selectively wrap and solubilize semiconducting SWNTs with specific diameters.…”
Section: (75) Swnt Dispersion and Morphological Characterizationmentioning
confidence: 99%
“…From AFM measurements, the nanotube length in the as-processed (7,5) SWNTs network is found to range from ~100 nm to ~1500 nm, with a SWNT surface density well above the percolation threshold and a maximum surface coverage ≈ 58%. Analysis of the field-effect charge transport measurements in the SWNT network using a two-dimensional -2 -plane and reveal the isotropic nature of the as-spun (7,5) SWNT networks.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations